Study of the Phenotype of Endothelial Cells in the Vessels of Uveal Melanoma - V. G. Likhvantseva; O. A. Anurova; S. E. Astakhova; M. V. Vereshchagina; V. E. Ovanesyan; E. V. Stepanova (Oftalʹmologiâ, 2023)
In tumor angiogenesis, two main mechanisms are officially recognized. They are: the formation of vascular structures by associations of endothelial cell precursors (PEK) or angioblasts from circulating peripheral blood (1) and vascular co-optation (2) using preexistent vessels. Determining the dominant phenotype of endothelial cells (EC) involved in the neoangiogenesis of uveal melanoma (UM) is very important due to the different sensitivity of different EC to antiangiogenic therapy and their biological differences. Circulating hemangioblasts of bone marrow origin (synonym: endothelial cell precursors, PEC) involved in the formation of vessels in the tumor can also originate from hematopoietic stem cells and, in conditions of an excess of proangiogenic growth factors, undergo “reverse differentiation” or “dedifferentiation”. This situation is extremely dangerous due to changes in the biological properties of EC: the rate of proliferation increases and high resistance to any type of interventional antiangiogenic therapy, including targeted antiangiogenic drugs, develops. In combination with high resistance to radiation therapy and chemotherapy of tumor cells, such a tumor becomes uncontrollable and quickly leads to death... The purpose of this study: to identify the phenotype of endothelial cells involved in UM angiogenesis by immunohistochemical analysis. The authors conducted immunohistochemical studies on paraffin blocks (n = 98) of enucleated eyes with UM. One of the recommended PEC markers was used: a monoclonal antibody to the VEGFR2-KDR/Flk-1 receptor. It was found that the expression of the VEGFR- 2/Flk-KDR-1 receptor took place only in 22.1 % of the UM. The receptor was expressed exclusively by endothelial cells (EC) of tumor vessels and was not expressed by UM cells. There was no basic expression of the receptor (at stage T1). Peak expression was observed at stage T2. At the next stages of the oncological process, there was a decline in expression. The mean IHC gradation of expression intensity also decreased from stage T2 to stage T4. Flk-positive and negative endothelial cells differed in size, shape, nature of communication with the vascular wall and the presence or absence of a nucleus in the cell. The authors concluded that both mechanisms of angiogenesis take place in UM. A small percentage (22.1 %) Flk+endothelial cells indicate that the dominant mechanism of angiogenesis in UM is co-optation of vessels based on preexistent, and the dominant population of EC is Flk-negative EC.